The income elasticity of mortgage loan demand. Issue 2 (27th February 2019) - Delis, Manthos D.; Hasan, Iftekhar; Tsoumas, Chris
Abstract: One explanation for the emergence of the housing market bubble and the subprime crisis is that increases in individuals' income led to higher increases in the amount of mortgage loans demanded, especially for the middle class. This hypothesis translates to an increase in the income elasticity of mortgage loan demand before 2007. Using applicant‐level data, we test this hypothesis and find that the income elasticity of mortgage loan demand in fact declines in the years before 2007, especially for the mid‐ and lower‐middle income groups. Our finding implies that increases in house prices were not matched by increases in loan applicants' income.